Rare mimic of pedal osteomyelitis in a patient with diabetes. Issue 11 (November 2016) - Kumar, S.; Kyi, M.; Wraight, P. R.
Abstract: Background: Diabetic foot infections are an important cause of hospitalization, health expenditure and mortality. Bone biopsy is the gold standard for diagnosing diabetic foot osteomyelitis1 but it is not routinely performed in most centres. Instead, a combination of history, examination, biochemical and radiological findings are used to make the diagnosis. Case Report: Here, we report a case mimicking diabetic foot osteomyelitis, where the histology was crucial in acquiring the correct diagnosis. Conclusion: The absence of ulceration in cases of presumed diabetic foot osteomyelitis should raise suspicion of potential rare mimics of osteomyelitis and bone biopsy should be considered to further evaluate the underlying etiology prior to any definitive surgical management. What's new?: Atypical presentations of suspected diabetic foot osteomyelitis should raise suspicion of potential rare mimics and be further investigated with pedal bone biopsy prior to any definitive surgical management.